Analyses of Plasmids Harbouring Quinolone Resistance Determinants in Enterobacteriaceae Members - Bayri Erac; Fethiye Ferda Yilmaz; Ismail Ozturk; Sabire Sohret Aydemir; Mine Hosgor-Limoncu (Polish Journal of Microbiology, 2017)
The aim of this study was to explore the plasmid characteristics of eight clinical Enterobacteriaceae strains containing extended broad spectrum beta-lactamases and plasmid-mediated quinolone resistance. Plasmids were transferred by conjugation or transformation and resistance determinants were investigated by PCR. We showed that at least one plasmid harbouring qnrB or qnrS determinant was transferred by conjugation in five isolates. QepA determinant was confirmed to be on a non-conjugative plasmid. We found at least one beta-lactamase gene in seven of the eight clinical isolates having plasmid-mediated quinolone resistance, which indicated that these two resistance determinants were mostly on the same conjugative plasmids.